Towards a global research program on food systems - CGIAR Research Program on Climate Change, Agriculture and Food Security; Future Earth (2014)
Future Earth is interested to establish a research area on food systems. This one day workshop, hosted by the CCAFS Coordinating Unit at the University of Copenhagen in collaboration with Future Earth, was intended to contribute to that aim. Two objectives were agreed for the meeting, namely (i) to identify some of the major research themes that are currently under-researched and (ii) to explore modalities for achieving greater synergy amongst current global research programmes on Food Systems. The facilitated workshop was attended by 44 invited participants who represented a wide range of research disciplines, institutions, nationalities and geographic spread and was structured around plenary presentations and working group discussion and feedback.